2011
DOI: 10.1007/s00404-011-1850-9
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of vulvar and vaginal cancer in Germany

Abstract: Due to a change in sexual behavior and an increased rate of HPV infection among younger women, increased incidence of both diseases has to be expected. The age-standardized mortality rate of vulvar carcinoma in Europe is stated at 0.7/100,000 women, and that of vaginal carcinoma at 0.4/100.000 women. To what extent the HPV-vaccination affects incidence and mortality rates is continually being observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
3
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 28 publications
2
41
3
2
Order By: Relevance
“…We also found that the incidence increased with age, as has been suggested by other authors [6,13,14,15,16]. However, our patients ranged in age from 15 to 98 years.…”
Section: Discussionsupporting
confidence: 70%
“…We also found that the incidence increased with age, as has been suggested by other authors [6,13,14,15,16]. However, our patients ranged in age from 15 to 98 years.…”
Section: Discussionsupporting
confidence: 70%
“…The highest incidence rates are reported in Latin America, whereas the lowest incidence rates were confirmed in Japan and China. Advanced age, cigarette smoking, low socioeconomic status, chronic inflammation, lichen sclerosus and immunosuppression are proven factors enhancing the development of type I vulvar cancer, which may occur without pervious VIN lesions [5,6]. Type II vulvar cancer primarily affects younger women (<50 years of age) as a result of the progression and invasion of VIN lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Vaginal cancer can develop at any age, but its highest incidence is observed in women over 65 years of age [6]. In younger females, glandular vaginal cancer can be the result of in utero exposure to diethylstilbestrol.…”
Section: Introductionmentioning
confidence: 99%
“…Although high risk HPV infection is a well-established cause of cervical cancer, but there is now growing evidence of HPV being a relevant factor in vulva and Vaginal cancers. HPV infection is associated with both of benign and malignant lesions and almost detected in the younger women rather than elder women (zur Hausen, 2002;De Vuyst et al, 2009;Ramet et al, 2010;Dittmer et al, 2011) In this study, HPV DNA detection was performed on section of paraffin-embedded biopsy. The frequency of HPV positive was detected to be 47.06% and 60% in vulva and Vaginal cancers, respectively.…”
Section: Discussionmentioning
confidence: 99%